ENHANCING CUSTOMER LOYALTY THROUGH ROLE NEUROMARKETING, AND SUSTAINABLE FOOD CONSUMPTION BEHAVIOR: A STUDY OF RESTAURANT PRODUCTS - Nursaidah; Hari Sukarno; Nurul Awwaliyah (Universitas Muhammadiyah Bengkulu, 2025)
The hotel industry growth, including restaurants, beside a positive impact on the economy, in other side it also has a negative impact on the environment. This research aims to examine the role of neuromarketing in mediating the influence of sustainable consumption behavior on consumer loyalty. This research classified as explanatory research. The population in the study were restaurant consumers at star hotels in Jember City. Sample determination was carried out by purposive sampling. Hypothesis test used Structural Equation Modeling (SEM) with the SmartPLS statistical software. The results show that sustainable consumption behavior has a positive and significant effect on neuromarketing. Sustainable consumption behavior has a positive and significant effect on consumer loyalty. And, neuromarketing has a positive and significant effect on consumer loyalty